EFEKTIFITAS MODEL PEMBELAJARAN TALKING STICK TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MAS DARUSSALAM KAMPUNG BANJIR - Lia Aulina Hasayangan Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
Abstract The aims of this study is know whether there is a significant influence of using talking stick learning model on students’ mathematic communication ability at the eleventh grade students of MAS Darussalam. This research was conducted by applying experimental method (one group pretest post test design) with sample 35 students and they were taken by using simple cluster random sampling technique. Observation and test were used in collecting the data. Based on descriptive analysis, it was found that: (a) the score of using talking stick learning model was 3.2 (very good category), b) the average of students’ mathematic communication ability before using talking stick learning model was 44.18 (poor category) and after using talking stick learning model was 71.90(good category). Furthermore, by using paired sample ttest and helping SPSS version 17, the result showed the significant value was less than 0.05 (0.000<0.05). It talking stick, there is a significant influence of using talking stick learning model on students’ mathematic communication ability at the eleventh grade students of MAS Darussalam Keywords: Talking Stick Learning Model, Communication Ability